Quantitative Health Impact Assessment of Environmental Exposures Linked to Urban Transport and Land Use in Europe: State of Research and Research Agenda - James Woodcock; Lambed Tatah; Paulo Anciaes; Zorana Andersen; Ronita Bardhan; Xuan Chen; Audrey de Nazelle; Ulrike Gehring; Stefan Gössling; Marco Helbich; Gerard Hoek; SM Labib; et al. (Current Environmental Health Reports, 2025)
In this article, we summarise recent developments, identify gaps, and propose a research agenda for quantitative health impact assessment (HIA) of environmental exposures linked to urban transport and land use. This is based on a workshop of 30 experts, complemented by targeted literature identified by participants to illustrate the state of research and practice gaps. The practice of quantitative HIA in urban transport and land use interventions covers a diverse range of methods, models, and frameworks. The selection of an appropriate model depends upon the use case, i.e., the research question, resources and expertise, and application. The plurality of models can be a strength if differences are explicit and their implications are understood. A major gap in most assessments and frameworks is the lack of equity consideration. This should be integrated into all stages of the HIA, considering exposures, susceptibility, disease burden, capacity to benefit, household budgets, responsibility for harm, and participation in the process. Scenarios of environmental exposures in urban transport and land use interventions are often overly simple, while the scenario design process of spatial planning is often opaque. Researchers should specify the involvement of stakeholders and the data, evidence, or behavioural model used to construct the scenario. Recent developments in exposure assessment (remote sensing and modelling) have increased the capacity to conduct HIAs for small geographies at scale. At the same time, advances in simulation have enabled the representation of behaviours at high spatial and temporal resolution. The combination can enable person-centric measures accounting for location, activities, and behaviours, with HIA proceeding ahead of epidemiology. Most HIAs still use Comparative Risk Assessment. This is suitable for estimating the disease burdens of environmental exposures, but more advanced longitudinal methods are better suited for studying interventions. Beyond health outcomes, well-being must be incorporated. The monetisation of health outcomes through welfare economics remains contentious. Representation of uncertainty is increasingly acknowledged. Value of Information methods can inform where new data collection would most efficiently reduce final result uncertainty. In the context of the climate crisis and related environmental limits, methods are needed that consider adaptation alongside mitigation and prevention and test robustness to an increasingly unstable future.

Scientific agenda for climate risk and impact assessment of West African cropping systems - M. Diancoumba; D. MacCarthy; H. Webber; F. Akinseye; B. Faye; F. Noulèkoun; A. Whitbread; M. Corbeels; N. Worou (Global Food Security, 2023)

Experimental infection trials with European North Atlantic ranavirus ( Iridoviridae ) isolated from lumpfish ( Cyclopterus lumpus , L.) - Felix Scholz; Niccolò Vendramin; Niels Jørgen Olesen; Argelia Cuenca; Tine Moesgaard Iburg; Luca Mirimin; Ian O'Connor; Neil M. Ruane; Hamish D. Rodger; Eugene MacCarthy (Journal of Fish Diseases, 2022)
European North Atlantic ranavirus (ENARV, Iridoviridae ), is a ranavirus species recently isolated from lumpfish ( Cyclopterus lumpus , L.), which are used as cleaner fish in Atlantic salmon ( Salmo salar ) farming in Northern Europe. This study aimed to investigate (1) the virulence of ENARV isolates from Ireland, Iceland and the Faroe Islands to lumpfish; (2) horizontal transmission between lumpfish; and (3) virulence to Atlantic salmon parr. Lumpfish were challenged in a cohabitation model using intraperitoneally (IP) injected shedders, and naïve cohabitants. IP challenge with isolates from Iceland (1.9 × 10 7 TCID 50 ml −1 ) and the Faroe Islands (5.9 × 10 7 TCID 50 ml −1 ) reduced survival in lumpfish, associated with consistent pathological changes. IP challenge with the Irish strain (8.6 × 10 5 TCID 50 ml −1 ) did not significantly reduce survival in lumpfish, but the lower challenge titre complicated interpretation. Horizontal transmission occurred in all strains tested, but no clinical impact was demonstrated in cohabitants. Salmon parr were challenged by IP injection with the Irish isolate, no virulence or virus replication were demonstrated. A ranavirus qPCR assay, previously validated for fish ranaviruses, was first used to detect ENARV in tissues of both in lumpfish and Atlantic salmon. This study provides the first data on the assessment of virulence of ENARV isolates to lumpfish and salmon, guidelines for the diagnosis of ENARV infection, and poses a basis for further investigations into virulence markers.

A Scientific Synthesis of Marine Protected Areas in the United States: Status and Recommendations - Jenna Sullivan-Stack; Octavio Aburto-Oropeza; Cassandra M. Brooks; Reniel B. Cabral; Jennifer E. Caselle; Francis Chan; J. Emmett Duffy; Daniel C. Dunn; Alan M. Friedlander; Heather K. Fulton-Bennett; Steven D. Gaines; Leah R. Gerber; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs) are a key tool for achieving goals for biodiversity conservation and human well-being, including improving climate resilience and equitable access to nature. At a national level, they are central components in the U.S. commitment to conserve at least 30% of U.S. waters by 2030. By definition, the primary goal of an MPA is the long-term conservation of nature; however, not all MPAs provide the same ecological and social benefits. A U.S. system of MPAs that is equitable, well-managed, representative and connected, and includes areas at a level of protection that can deliver desired outcomes is best positioned to support national goals. We used a new MPA framework, The MPA Guide, to assess the level of protection and stage of establishment of the 50 largest U.S. MPAs, which make up 99.7% of the total U.S. MPA area (3.19 million km 2 ). Over 96% of this area, including 99% of that which is fully or highly protected against extractive or destructive human activities, is in the central Pacific ocean. Total MPA area in other regions is sparse – only 1.9% of the U.S. ocean excluding the central Pacific is protected in any kind of MPA (120,976 km 2 ). Over three quarters of the non-central Pacific MPA area is lightly or minimally protected against extractive or destructive human activities. These results highlight an urgent need to improve the quality, quantity, and representativeness of MPA protection in U.S. waters to bring benefits to human and marine communities. We identify and review the state of the science, including focal areas for achieving desired MPA outcomes and lessons learned from places where sound ecological and social design principles come together in MPAs that are set up to achieve national goals for equity, climate resilience, and biodiversity conservation. We recommend key opportunities for action specific to the U.S. context, including increasing funding, research, equity, and protection level for new and existing U.S. MPAs.

Estimates of Blood Lead Levels (BLLs) for Children in Coastal Madagascar: Accounting for Dietary Uptake of Lead (Pb) - D. Brad Akers; Adaline Buerck; Michael F. MacCarthy; Jeffrey A. Cunningham; James R. Mihelcic (Exposure and Health, 2020)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Oxidative stress is associated with late‐stage amoebic gill disease in farmed Atlantic salmon ( Salmo salar L.) - M Marcos‐López; C Ruiz Espinosa; H D Rodger; I O'Connor; E MacCarthy; M A Esteban (Journal of Fish Diseases, 2018)

Piscine myocarditis virus detected in corkwing wrasse ( Symphodus melops ) and ballan wrasse ( Labrus bergylta ) - F Scholz; N M Ruane; T Morrissey; M Marcos‐López; S Mitchell; I O'Connor; L Mirimin; E MacCarthy; H D Rodger (Journal of Fish Diseases, 2018)

Low-cost water-lifting from groundwater sources: a comparison of the EMAS Pump with the Rope Pump - Michael F. MacCarthy; Jacob D. Carpenter; James R. Mihelcic (Hydrogeology Journal, 2017)

Evaluation of Non-destructive Molecular Diagnostics for the Detection of Neoparamoeba perurans - Jamie K. Downes; Megan L. Rigby; Richard S. Taylor; Ben T. Maynard; Eugene MacCarthy; Ian O'Connor; Mar Marcos-Lopez; Hamish D. Rodger; Evelyn Collins; Neil M. Ruane; Mathew T. Cook (Frontiers in Marine Science, 2017)

Modeling the effect of seasonal climate variability on the efficiency of mineral fertilization on maize in the coastal savannah of Ghana - D. S. MacCarthy; P. B. I. Akponikpe; S. Narh; R. Tegbe (Nutrient Cycling in Agroecosystems, 2015)

Simulating impact of seasonal climatic variation on the response of maize (Zea mays L.) to inorganic fertilizer in sub-humid Ghana - B. Y. Fosu-Mensah; D. S. MacCarthy; P. L. G. Vlek; E. Y. Safo (Nutrient Cycling in Agroecosystems, 2012)

Farmers’ perception and adaptation to climate change: a case study of Sekyedumase district in Ghana - B. Y. Fosu-Mensah; P. L. G. Vlek; D. S. MacCarthy (Environment, Development and Sustainability, 2012)